Paradoks Hukum Perdagangan Indonesia: Antara Green Economy dan Ekspor Sumber Daya Alam yang Eksploitatif: The Legal Paradox of Indonesia’s Trade: Between Green Economy and Exploitative Natural Resource Exports - Vikri Pramana Putra; Januardo Sulung Partogi Sihombing (Universitas Semarang, 2025)
This study aims to analyze and formulate legal strategies that reconcile Indonesia’s natural resource (NR) export interests with its commitment to sustainable development as outlined in the Sustainable Development Goals (SDGs). The research is driven by the escalating tension between short-term economic growth fueled by raw commodity exports and the global imperatives of environmental sustainability and green economy transition. Employing a normative juridical method combined with qualitative analysis, this study critically examines the substance and implementation of the Job Creation Law, the Mining Law, and the Plantation Law, assessing their coherence with principles of ecological justice, environmental governance, and green trade. The findings reveal that Indonesia’s current regulatory framework remains sectoral and predominantly economistic, lacking substantive integration of sustainability principles and resulting in regulatory fragmentation across sectors. The novelty of this research lies in its conceptual synthesis of international trade law, environmental law, and SDGs into a unified legal development framework, supported by a transformative reform model aimed at embedding sustainability into national legal systems. This study concludes that ecological mainstreaming, institutional harmonization, adoption of green-certified export instruments, and the incorporation of Islamic legal values and local wisdom in resource governance are essential to achieving ecological justice and intergenerational equity in Indonesia’s natural resource management. Penelitian ini bertujuan untuk menganalisis dan merumuskan strategi hukum yang mampu menyeimbangkan kepentingan ekspor sumber daya alam (SDA) Indonesia dengan komitmen terhadap pembangunan berkelanjutan sebagaimana diamanatkan dalam Sustainable Development Goals (SDGs). Urgensi penelitian ini dilatarbelakangi oleh meningkatnya ketegangan antara pertumbuhan ekonomi jangka pendek yang didorong oleh ekspor komoditas mentah dan tuntutan global terhadap keberlanjutan lingkungan serta transisi menuju ekonomi hijau. Metode penelitian menggunakan pendekatan yuridis normatif yang dipadukan dengan analisis kualitatif untuk mengkaji substansi dan implementasi tiga regulasi utama Undang-Undang Cipta Kerja, Undang-Undang Minerba, dan Undang-Undang Perkebunan serta menilai kesesuaiannya dengan prinsip keadilan ekologis, tata kelola lingkungan, dan standar perdagangan hijau. Hasil penelitian menunjukkan bahwa rezim regulasi nasional masih bersifat sektoral dan ekonomistik, belum sepenuhnya mengintegrasikan prinsip keberlanjutan secara substantif, dan menimbulkan konflik pengaturan lintas sektor. Kebaruan penelitian ini terletak pada sintesis konseptual antara hukum perdagangan internasional, hukum lingkungan, dan SDGs dalam satu kerangka pembangunan hukum yang terpadu, disertai model reformasi hukum transformatif untuk mengarusutamakan keberlanjutan dalam sistem hukum nasional. Penelitian ini menyimpulkan bahwa pengarusutamaan ekologi, harmonisasi kelembagaan lintas sektor, penerapan instrumen ekspor bersertifikat hijau, serta pengintegrasian nilai-nilai hukum Islam dan kearifan lokal dalam tata kelola sumber daya alam merupakan langkah strategis menuju keadilan ekologis dan tanggung jawab antargenerasi dalam pengelolaan SDA Indonesia.